The Inconsistency Between Women's Preference and Actual Mode of Delivery in China: Findings From a Prospective Cohort Study - Wu, Jing; Feng, Li; Zhang, Hongwei; Guo, Li; Pérez-Escamilla, Rafael; Hu, Yifei (Frontiers in Public Health, 2022)
Background: Previous studies have found that the rates of cesarean preference were much lower than the actual rates of cesarean births in China. We aimed to observe this inconsistency between preferred and actual modes of delivery and the factors associated with the inconsistency. Methods: We conducted a prospective cohort study at the maternity hospital with largest number of deliveries in Beijing. We collected data through a questionnaire applied in the outpatient department, and medical records from the hospital’s information system. Unconditional logistic regression was used to identify factors influencing the inconsistency between preferred and actual delivery mode. Results: The rates of actual cesarean section and of cesarean preference were 41% and 17%, respectively (χ2=82.9, P<0.0001). The overall inconsistency rate was 31%, with 119 women preferred vaginal delivery but experienced cesarean section, accounting for 67% women undergoing cesarean section. Risk factors for this inconsistency between preferred vaginal delivery and actual cesarean section included: maternal obesity, receiving assisted reproduction, having an abnormal amniotic fluid volume, and fetal distress. Pre-labor rupture of membranes was a unique factor associated with such inconsistency between cesarean section preference and vaginal delivery at delivery. Conclusions: The inconsistent rate between preferred delivery at late pregnancy and actual delivery is high in China. Further research is needed to understand how to lower cesarean rates in China, taking maternal preferences for vaginal deliveries into account.